2018
DOI: 10.1523/jneurosci.1740-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Neuroinflammation Induced by Influenza A Virus Infection and the Impact on Hippocampal Neuron Morphology and Function

Abstract: Acute influenza infection has been reported to be associated with neurological symptoms. However, the long-term consequences of an infection with neurotropic and non-neurotropic influenza A virus (IAV) variants for the CNS remain elusive. We can show that spine loss in the hippocampus after infection with neurotropic H7N7 (rSC35M) and non-neurotropic H3N2 (maHK68) in female C57BL/6 mice persists well beyond the acute phase of the disease. Although spine number was significantly reduced at 30 d postinfection (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
207
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(228 citation statements)
references
References 99 publications
14
207
3
4
Order By: Relevance
“…In the reversal phase of the Morris water maze test, the platform was moved to the opposite quadrant (SW) and the rats were trained for another 3 consecutive days. This test needs cognitive flexibility [65]. The results indicated that escape latency was significantly higher in I/R and I/ R + DMSO tested groups compared to control, in addition here injection of MK-4 reversed the phenotype in I/R animals (two-way RM ANOVA: F Escape latency (3, 20) = 22,58, p < 0.001, Fig 3G).…”
Section: Positive Effect Of Mk-4 Administration On Behavioral Deficitmentioning
confidence: 80%
“…In the reversal phase of the Morris water maze test, the platform was moved to the opposite quadrant (SW) and the rats were trained for another 3 consecutive days. This test needs cognitive flexibility [65]. The results indicated that escape latency was significantly higher in I/R and I/ R + DMSO tested groups compared to control, in addition here injection of MK-4 reversed the phenotype in I/R animals (two-way RM ANOVA: F Escape latency (3, 20) = 22,58, p < 0.001, Fig 3G).…”
Section: Positive Effect Of Mk-4 Administration On Behavioral Deficitmentioning
confidence: 80%
“…Several studies have shown that influenza A can be associated with encephalitis, Reye's syndrome, febrile seizure, Guillain-Barré syndrome, acute necrotizing encephalopathy and possibly acute disseminated encephalomyelitis (ADEM) [153][154][155][156][157][158]. Animal models have shown that, using either the olfactory route or vagus nerve, influenza A virus may have access to the CNS and alter the hippocampus and the regulation of neurotransmission, while affecting cognition and behavior as long-term sequelae [8,69,[159][160][161][162]. The influenza A virus has also been associated with the risk of developing Parkinson's disease (PD) [151] and has recently been shown to exacerbate experimental autoimmune encephalomyelitis (EAE), which is reminiscent of the observation that multiple sclerosis (MS) relapses have been associated with viral infections (including influenza A) of the upper respiratory tract [163][164][165].…”
Section: Respiratory Viruses With Neuroinvasive and Neurotropic Propementioning
confidence: 99%
“…Herpes simplex viruses can spread via the dorsal root ganglia to the autonomic ganglia of the enteric nervous system in the colon [52]. Influenza A virus may have access to the CNS and alter the hippocampus function via the vagus nerve, affecting cognition and behavior [53,54]. Although there is no direct evidence to show that SARS-CoV-2 can enter the CNS retrogradely via the intestinal branch of the vagus nerve, the disrupted gastrointestinal environment may influence the integrity of the BBB through immune, neural, and humoral pathways, thus facilitating the movement of the peripheral virus into the CNS.…”
Section: Digestive Tract Routementioning
confidence: 99%